Neuro-Myelitis Optica Spectrum Disease (NMOSD) - Alkhatib, Ahed J (PSM Microbiology, 2023)
Neuromyelitis optica spectrum disorder (NMOSD) is a rare autoimmune disease that affects the central nervous system. It is characterized by inflammation of the optic nerve and spinal cord, which can cause vision loss, muscle weakness, and other neurological symptoms. The main objective of this study was to conduct a review study of this disease from different perspectives including an overview of the disease, prevalence, diagnosis, symptoms, and treatment. It can be concluded that NMOSD is a rare autoimmune disorder that primarily affects the optic nerve and spinal cord. Studies on NMOSD have provided important insights into the pathogenesis, diagnosis, and treatment of the condition.